Economic Boom or Ecologic Doom? : Using Spatial Analysis to Reconcile Road Development with Forest Conservation - Barra, Alvaro Federico; Burnouf, Mathilde; Damania, Richard; Russ, Jason (Washington, DC: World Bank, 2016)
The natural endowment of the Democrat Republic of Congo, in the form of land, minerals, and forests, is unparalleled. The right mix of policies has the potential to unleash incentives that could transform the economy. However, transport infrastructure in the DRC is amongst the sparsest and most dilapidated in the world, and this lack of infrastructure is likely a significant constraint to growth. This work considerably advances the information that is available to infrastructure planners, and provides methodologies that could be used to make more informed decisions to identify trade-offs between economic growth and environmental endangerment. The approach draws from the state-of the art across a variety of disciplines – spatial (GIS) analysis, spatial econometrics, economic theory, and conservation biology – to create an approach that can guide the location and level of investments by estimating benefits and environmental costs at a highly disaggregated spatial scale.